2009
DOI: 10.1007/s00125-008-1244-0
|View full text |Cite
|
Sign up to set email alerts
|

Childhood BMI trajectories and the risk of developing young adult-onset diabetes

Abstract: Aims/hypothesis The aim of this study was to examine the effects of childhood BMI growth dynamics on the risk of developing young adult-onset type 1 and type 2 diabetes. Methods Finnish national healthcare registers were used to identify individuals with diabetes diagnosed between 1992 and 1996 at 15-39 years of age. Non-diabetic control participants were chosen from the National Population Registry. Anthropometric measurements were obtained from the original child welfare clinic records. Only the case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…First, there is no information on the extent to which genetic and environmental factors may influence the rate-of-change of adolescent BMI. Understanding the contribution of the underlying factors in BMI trajectories across this period is essential as it may help in the prevention of obesity and its comorbidities later in life (Lammi et al 2009). While findings have clearly suggested the presence of specific genetic influences accounting for the change of BMI across middle and late adulthood (Hjelmborg et al 2008;Ortega-Alonso et al 2009), it remains unknown whether this is also the case in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…First, there is no information on the extent to which genetic and environmental factors may influence the rate-of-change of adolescent BMI. Understanding the contribution of the underlying factors in BMI trajectories across this period is essential as it may help in the prevention of obesity and its comorbidities later in life (Lammi et al 2009). While findings have clearly suggested the presence of specific genetic influences accounting for the change of BMI across middle and late adulthood (Hjelmborg et al 2008;Ortega-Alonso et al 2009), it remains unknown whether this is also the case in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Finnish studies have shown that those children who presented subsequently with type 1 diabetes were not only heavier but also taller in infancy (18,35), although there were no significant differences in birth weight or length. A recent survey showed that those subjects who presented with type 1 diabetes between 15 and 39 y of age had a higher gain in their body mass index during infancy than unaffected controls (36).…”
Section: Infant Growthmentioning
confidence: 99%
“…Obese children often become obese adults (2), and obese children have a greater risk of developing hypertension, dyslipidemia, and impaired glucose tolerance or type 2 diabetes (3,4). Childhood adiposity has a significant bearing on subsequent adult health and disease, and a higher BMI in childhood is associated with adult-onset diabetes (5,6), hypertension (7,8), visceral and s.c. fat mass (9), metabolic syndrome (10), and coronary heart disease (11). Similarly, elevated fasting plasma insulin (FI) level in childhood is associated with the adult metabolic syndrome (10,12).…”
mentioning
confidence: 99%